The color of the skin. 2. Hypermelanosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
This chapter includes the diseases which are responsible for melanotic macules of the skin. According to the definition of patch (see pag. 9 of the book), the chapter will not treat the diseases which present hypermelanotic and infiltrated skin. Nevus cells nevi and other diseases associated with melanotic plaques of the skin will be therefore treated in another chapter. (...).